Analisis Koreksi Fiskal Atas Laporan Keuangan Komersial Pada PT. Aneka Tambang (Persero) Tbk Tahun 2020-2021 - Ayu, Rhea Samantha; Murti, Galuh Tresna; Mamola, A. Rendy Sandra; Rachmawati, Restika Okta (University of Merdeka Malang, 2025)
The largest source of state revenue comes from taxes, including Corporate Income Tax (PPh Badan) imposed on corporate income within a year.